2010
DOI: 10.1097/prs.0b013e3181d62aef
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Analysis of Bony versus Soft-Tissue Reconstruction for Posterior Mandibular Defects

Abstract: With careful selection, good reconstructive results after posterior mandibular resection can be achieved with vascularized bone flap or soft-tissue free flaps. In appropriate candidates, vascularized bone flap reconstruction may result in better postoperative occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 11 publications
3
65
0
Order By: Relevance
“…Good results with soft-tissue reconstruction alone can be achieved for posterior mandibular defects. 14,15 Reconstructions for combined regions II and III are similar but need to extend further posteriorly to the region of the temporal bone (Fig. 6).…”
Section: Discussionmentioning
confidence: 94%
“…Good results with soft-tissue reconstruction alone can be achieved for posterior mandibular defects. 14,15 Reconstructions for combined regions II and III are similar but need to extend further posteriorly to the region of the temporal bone (Fig. 6).…”
Section: Discussionmentioning
confidence: 94%
“…Reconstruction of bone and soft tissue defects with well-vascularized flaps not only provides reliable coverage, but it helps control infection while improving function and aesthetics as well. 17 In our series, more than half of the patients were able to tolerate a full oral diet, one fourth of the patients required supplemental tube feeding, and 16% of the patients remain tube-feeding dependent mainly due to trismus, loss of dentures, loss of appetite, and poor overall functional status. It should be noted that all patients were tube-feeding dependent before surgery.…”
Section: Discussionmentioning
confidence: 96%
“…The advantages of bone reconstructions are that they may minimize jaw deviation, provide better occlusion, and slightly better definition of the mandible contour compared to soft tissue flaps, and provide the possibility of osteointigrated dental implants; however, functional outcomes are comparable. 17 Type IIb Defects. When the soft tissue defect involves both intraoral and external skin, a throughand-through defect, it is classified as type IIb.…”
Section: Discussionmentioning
confidence: 99%
“…The reconstructive option is to either utilize the free osteocutaneous flap or the free tissue transfer alone. Hanasono et al [22] compared the outcomes of these two modalities in restoring posterior mandibular defects they found that, while soft tissue free flap alone may achieve reasonable aesthetics, masticatory function, and degree of mouth opening, in young patients with good surgical prognoses, the vascularized bone flap is preferred because of the more predictable dental function.…”
Section: Reconstructive Strategiesmentioning
confidence: 99%